Axillary Nodal Staging with Contrast-Enhanced Ultrasound - Sharma, Nisha (Curr Breast Cancer Rep, 2017)
PURPOSE OF REVIEW: Axillary staging in the context of breast cancer is a contentious topic due to the varied practices across UK, Europe, and America. The ACOSOG Z0011 trial has questioned the role of axillary ultrasound in women with breast cancer. Published data has shown that women with ultrasound-positive lymph nodes have a worse prognosis than those with ultrasound-negative lymph nodes. Axillary ultrasound is limited as the sentinel lymph node (SLN) cannot be identified using B-mode ultrasound; however, with the advent of contrast-enhanced ultrasound (CEUS), this has now changed. RECENT FINDINGS: The published literature has shown that the sentinel lymph node can be identified using CEUS. The rates are equivalent to blue dye alone but currently inferior to the dual technique of sentinel lymph node biopsy. There are several different contrast agents that can be used and the agents that remain in the sentinel lymph node for longer can identify areas of poor enhancement, allowing for targeted biopsy. SUMMARY: CEUS has the potential to revolutionize the way we manage the axilla in the future and may even replace surgical staging.